HUBUNGAN POLA ASUH DENGAN PERKEMBANGAN ANAK BALITA DI WILAYAH KERJA PUSKESMAS ANDALAS PADANGHUBUNGAN POLA ASUH DENGAN PERKEMBANGAN ANAK BALITA DI WILAYAH KERJA PUSKESMAS ANDALAS PADANG - Helda Helda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Development and growth disorders are a heslth issues that commonly found in societ.From the information in Andalas PHC padang there were 10 childeren who suffered stunted growth. The purpose of this study was to determine the relationship of parenting with the the growth of children under five years In The Work Area Of Andalas PHC Padang In 2020. The desain of this research is an analytic with case control approach researchers distinguish populations into 2 of the 10 cases and 20 controls by matching way. The study was conducted in Januari- Juni 2020 and using research instruments questionnaire. Information analysis techniques used were univariate and bivariate analysis using chi-square test. The result shows that the case and the control group negative parenting pattern as much 80% and 25% with p value = 0.007 with OR 12 times. It cen be concluded that there are a relationship of parenting on the childeren development under five yeares in the work area of Andalas PHC padabg in 2020. Advice to parents should be briefed or informed about parenting parents in monitoring the growth of children.